Formation of nano-twinned structure in Ti3AlC2 induced by ion-irradiation. (15th April 2017) - Yang, Tengfei; Wang, Chenxu; Liu, Wulong; Liu, Shaoshuai; Xiao, Jingren; Huang, Qing; Xue, Jianming; Yan, Sha; Wang, Yugang
Abstract: In the present study, a nano-twinned microstructure is found in ion irradiated-Ti3 AlC2 by the characterizations of high-resolution transmission electron microscopy and electron diffraction, combined with grazing incidence X-ray diffraction. No obvious difference in chemical composition was observed between pristine and irradiated samples. Ti3 AlC2 transforms to a cation-disordered Ti-Al-C system with the rocksalt structure after ion irradiation, in which Ti and Al atoms randomly occupy the cation sites and C atoms occupy the anion sites with occupancy of 0.5. The as-irradiated Ti3 AlC2 exhibits a nano-twinned structure and the twin thickness is in the range between 2 and 10 nm. Most of defects are located at or near the twin boundaries, which may be attributed to the segregation of Al. Based on the structural variations of complex oxides induced by ion irradiation and stability of solid solution (Ti, Al) x C, it is assumed that Ti3 AlC2 has a natural tendency to accommodate the defects through the chemical order to chemical disorder, low symmetry to high symmetry structural transformation. The formation mechanisms of the nano-twinned structure are related to the irradiation-induced antisite defect of cations, disorder of C atoms, and lattice structure characteristic of Ti3 AlC2 . Because the nano-twinned structure may significantly improve the irradiation tolerance of Ti3 AlC2 we study its stability under irradiation of Au ions at ∼150 dpa. Only a moderate increase in the twin thickness is found and the nano-twinned structure is basically retained, which demonstrates the great stability of nano-twinned structure and makes Ti3 AlC2 a very promising irradiation tolerant material for advanced nuclear systems. Graphical abstract: Image 1